Numerical Study of Natural Convective Heat and Mass Transfer in an Inclined Porous Media - Latreche, A.; Djezzar, M. (Engineering, Technology & Applied Science Research, 2018)
In this study, two dimensional natural convection heat and mass transfer generated in an inclined rectangular porous cavity filled with Newtonian fluid has been investigated numerically. The cavity is heated and cooled along horizontal walls while the solutal gradient is imposed horizontally. The physical model for the momentum conservation equation makes use of the Darcy model, and the set of coupled equations is solved using a finite volume approach. The successive-under-relaxation (SUR) method is used in the solution of the stream function equation. The results are presented graphically in terms of streamlines, isotherms and iso-concentrations. The heat and mass transfer rate in the cavity is measured in terms of the average Nusselt and Sherwood numbers for various non-dimensional parameters.